2022
DOI: 10.1007/s40843-022-2153-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent advance in three-dimensional porous carbon materials for electromagnetic wave absorption

Abstract: With the increasingly serious electromagnetic wave (EMW) pollution, the development of high-performance EMW absorbing materials (EWAMs) has become a hot topic. Carbon-based EWAMs have excellent chemical stability, high electrical conductivity, and strong dielectric loss. In particular, three-dimensional (3D) porous carbon-based EWAMs have been widely developed in the EMW absorption field. The 3D porous structure not only reduces the materials' mass density, but also improves the multiple reflections of inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 160 publications
0
17
0
Order By: Relevance
“…8 Further, the advantages of functionalized CNTs include their easy dispersibility in an aqueous solvent, tunability of the functional group, and chemical modification that gives an add-on effect for becoming excellent microwave absorbing materials. 9 Therefore, researchers have developed nanocomposites by mixing CNTs with graphene, MXene, and cellulose nanofillers to get better electromagnetic interference shielding efficiency. [8][9][10][11][12] The selection of MWCNTs is mainly governed by their excellent electron conductivity resulting from highly delocalized π-conjugated electrons and large surface areas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Further, the advantages of functionalized CNTs include their easy dispersibility in an aqueous solvent, tunability of the functional group, and chemical modification that gives an add-on effect for becoming excellent microwave absorbing materials. 9 Therefore, researchers have developed nanocomposites by mixing CNTs with graphene, MXene, and cellulose nanofillers to get better electromagnetic interference shielding efficiency. [8][9][10][11][12] The selection of MWCNTs is mainly governed by their excellent electron conductivity resulting from highly delocalized π-conjugated electrons and large surface areas.…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, researchers have developed nanocomposites by mixing CNTs with graphene, MXene, and cellulose nanofillers to get better electromagnetic interference shielding efficiency. [8][9][10][11][12] The selection of MWCNTs is mainly governed by their excellent electron conductivity resulting from highly delocalized π-conjugated electrons and large surface areas. However, the brittleness and poor mechanical properties of the freestanding CNT paper in the absence of binders, due to the lack of strong interaction, severely constrain its practical application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these plentiful materials, carbon materials such as carbon nanotubes, carbon black, graphite flakes, carbon fibers and filaments have attracted increasing interest and have caught people's attention due to their unique features such as diverse forms, light weight and tunable electrical conductivity and dielectric properties. 17,[19][20][21][22][23] In addition to composition, structure is another vital factor for improving the absorption performance of microwave absorbers. [24][25][26][27] It has been found that the hollow structure optimizes impedance matching and makes it easier for EMW to enter the absorbers and be dissipated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, electromagnetic interference (EMI) shielding materials as well as EMW absorbing materials (EWAMs) emerged as the times require and attracted increasing attention. [ 5‐9 ] Although metallic and magnetic materials have displayed impressive performance in the fields of EMW shielding and absorbing, [ 10‐12 ] high density and easy corrosion become the shackles for them to further expand the application area, especially those scenes that are extremely sensitive to weight, such as portable or wearable devices and aerospace equipment.…”
Section: Introductionmentioning
confidence: 99%